A novel fluorescent probe derived from isophorone and its application in imaging in vivo hypoxia. (September 2022) - Guo, L.; Wang, P.; Chen, H.; Fan, X.; Zhu, H-l.; Li, Z.
Abstract: Herein, an isophorone-derived fluorescent probe, ARP, was developed to realize the imaging of in vivo hypoxia under the catalysis of the typical enzyme AzoR. Under the excitation at 456 nm, the detecting system with ARP could exhibit a red emission signal at 638 nm. ARP indicated advantages including high sensitivity (LOD = 0.37 Eq), high selectivity, anti-interference ability and wide pH adaption (3.0–12.0). Moreover, ARP could image the aggravation of the hypoxia in both the incubating oxygen percentage scale and the time scale in living cells. The AzoR-activated mechanism was convinced by the experimental result of adding inhibitors and illustrated by the molecular docking simulation. ARP could co-locate with the commercial dyes in the endoplasmic reticulum (ER), lysosomes, and mitochondria, which meant that ARP might be sensitive to the occurrence of the oxidation-reduction process or the passage through the intracellular membranes. Further, ARP achieved the imaging of hypoxia in both mice tumor model as well as tying model. ARP could distinguish the tumor site or the tied-up position according to the hypoxia extent. Therefore, this work raised a new trial for the imaging of the hypoxia, and might be helpful in future designs of more pragmatic fluorescent implements. Highlights: A novel fluorescent probe for imaging in vivo hypoxia under the catalysis of AzoR. Advantages including red emission, reliable linear range, high sensitivity, high selectivity, wide pH adaption. Locating in endoplasmic reticulum, lysosomes, and mitochondria to visualize the oxidation-reduction process. Achieving the imaging of hypoxia in both mice tumor model and tying model.